Fatwa MUI Tentang Musyarakah, Penggunaan Istilah, Dalil, Metode Serta Sistematika Fatwa - A, Asna; Hartika, Ika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the application of akad muarakah, Shariah Financial Institutions (SFIs) agree to melt some of the assets they own jointly with customers to implement a specific venture. The proceeds of the effort will be shared between LKS and the customer based on the percentage of contributions made, both cash and non-cash. Such a practice is commonly known as the term yield sharing. To provide a sense of security for all parties involved in this practice, the National Shari'ah Council (NSN) which is part of the Indonesian Ulema Assembly (MUI) has issued fatwa MUI No. 8/DSN-MUI/IV/2000. In the Fatwa has been discussed about everything related to muarakah starting from ijab qabul, capital specifications, division of labor to profits and losses that all parties must bear. To accommodate muarakah transactions, the Indonesian Accounting Association (IAI) has issued Financial Accounting Standards Statement (PSAK) number 106 in 2007 which regulates in detail the accounting of muarakah transactions. MUI fatwa no 8/DSN-MUI/IV/2000 is certainly one of the foundations of the formation of PSAK 106 on muyarakah.